Enzymatic Markers of Pulmonary Inflammation in Tracheal Wash Fluid in Racehorses: Alkaline Phosphatase and Lactate Dehydrogenase - Kumaş, Cihan (2021)
Background: Diagnosis of the lower airway diseases (LAD) in horses relies on clinical signs, endoscopic examination and cytologic evaluation of lower respiratory tract flushing fluids as well. Specific enzyme activities in respiratory tract fluids of horses could be used as useful indicators in lower airway disorders. The main goal of the study was to evaluate the diagnostic usefulness of alkaline phosphatase (ALP) and lactate dehydrogenase (LDH) enzyme activites in tracheal wash (TW) fluids of horses with lower respiratory tract inflammation and/or damage and also in distinguishing of non-septic and septic inflammation in racehorses with LAD.Materials, Methods & Results: A cross-sectional study was conducted in racehorses. TW fluid samples were obtained from 83 racehorses (71 with lower airway diseases and 12 healthy controls) for the study. The One-Way ANOVA Test was used for the significance analysis of the differences between the groups in showing the normal distribution of blood serum ALP and LDH properties. Kruskal Wallis H Test and Tamhane T2 test were used for the significance analysis of the differences between the groups of tracheal ALP and LDH properties, which were not normally distributed.  The sampled horses were classified into 3 groups as healthy control, non septic neutrophilic inflammation (NS-LAD) and septic neutrophilic inflammation (S-LAD) according to the tracheal mucus scores determined during endoscopic examination, clinical signs, cytologic and bacteriologic examination of collected TW samples. According to cytology results normal neutrophil levels (< 20%) were determined in the heatlhy control group (14.5%). However, increased neutrophil levels (≥ 20% and ≥ 80%) were encountered in the NS-LAD (61.4%) and S-LAD (24.1%) groups respectively. Also, the signs of degenerative changes and presence of intracellular bacteria in the neutrophil cells in the S-LAD group was observed. Bacteriologic analysis of the samples revealed Streptococcus equi subsp. zooepidemicus was the most prevalent agent (85.6%) followed by Escherichia coli (4.8%), Staphylococcus aureus (4.8%) and Klebsiella pneumoniae (4.8%). ALP and LDH enzyme activities of TW fluid were found to be significantly higher in racehorses with LAD compared with healthy controls (P < 0.01). On the other hand, a significant difference was also determined for LDH levels between NS-LAD and S-LAD cases determining with cytological and bacteriological examination (P < 0.01). No statistically significant difference was found between NS-LAD and S-LAD group. Serum ALP and LDH levels of racehorses revealed no significant difference between each study groups.Discussion: Respiratory system diseases have been known to be one of the main causes of training disruption and interruption of racing events in racehorses. Specifically, LAD is the most frequently diagnosed disorder in racehorses evaluated for poor performance. In the present study established for determining the usefulness of ALP and LDH enzyme levels in the TW samples of horses with lower respiratory tract inflammatory disorders. It was concluded that ALP and LDH enzyme activities of TW fluid could be considered as indicators of pulmonary inflammation and/or damage and LDH enzyme activity is thought to be useful in distinguishing neutrophilic non-septic and septic pulmonary inflammation in racehorses with LAD. On the other hand, data obtained from the study indicated that TW fluid ALP activity was not enough statistically to differenatiate horses with non-septic and septic lower airway inflammation.